Face Recognition Based on Attendance Management System (International Journal of Innovative Research in Computer Science & Technology, 2020)
Attendance is very important task for an  organization like school, colleges, companies etc. Taking of  attendance manually is very time consuming. It takes up to  5 to 20 minutes and it depends upon the number of students  in a class. Now a day’s technology become more advance,  so we have to use biometric system for attendance because it  takes very less time as compared to taking attendance  manually. In this project we are going to make an  attendance system using face recognition. There are many  algorithms by which we can make an attendance system  using face recognition. In this project we use Viola-Jones  Algorithm and Local Binary Pattern Histogram (LBPH)  Algorithm. Viola-Jones algorithm is used for face detection  and Local Binary Pattern Histogram is used for samples  training and face recognition
Keywords: Viola-Jones Algorithm; Linear Binary Patterns Histograms (LBPH); Python; Face Detection; Face Recognition